A systematic review on linking community livelihood in social forestry with food security - Hardawati Yahya; H Mohd Amir; W Lintangah; ‪Diana Demiyah Mohd Hamdan; Fazlini Mohd Fadzwi; G J Thomas (2022)
Food security issues, particularly forest resources, have gained increasing worldwide attention over the past few years. Although studies have discussed various food security contributions, few have addressed the connection between community livelihood with food security, particularly in social forestry areas. Thus, the study aims to address the gap from an overview of community livelihood and food security in various Asian countries. The study retrieved approximately 142 articles from different databases and filtered 71, highlighting 30 case studies related to social forestry and food security, published between 2010 and 2021 cross schemes in Asia. The key indicators of community livelihood and food security mainly stated access to forest area, consumption of forest resources and non-timber forest products. The findings could improve future planning and management of social forestry and enhance food security for rural development and community livelihood. Ultimately, the study proposed a framework of forest-food security linkages, specifically for social forestry areas.